Big Steps in a Big Country : Brazil Makes Fast Progress Toward EFA - World Bank (Washington, DC, 2012)
By the year 2000, Brazil had almost achieved universal primary enrollment for Grades 1-4, and more than 50 million Brazilians were enrolled in the country's education system. From 1970 to 2000, 32 million additional students entered school, two-thirds of them during the last two decades. Over a five-year period (1996-2000), while primary schooling continued to make important gains, enrollments in secondary and tertiary education in Brazil grew at the astonishing rate of 43% and 44% respectively. Many developing countries face problems with age-grade distortion. Largely because of high repetition rates, age-grade distortion in Brazil is about 10 percent country-wide, and almost 40 percent in the northeastern part of the country. An innovative program called Accelerated Learning has been implemented to address this issue. Under this program, the federal government finances the creation of special classes for over-aged students with the objective of reducing the age-grade distortion and freeing up space in public schools. By year 2000 there were already 1.2 million students enrolled in accelerated learning programs in all Brazilian states.